2021
DOI: 10.1016/j.atherosclerosis.2021.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) levels and atherosclerotic plaque characteristics in the carotid artery: The Plaque at RISK (PARISK) study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 44 publications
4
15
0
3
Order By: Relevance
“…In women, elevated plasma Lp(a) levels were associated with higher prevalence of IPH and in men, elevated Lp(a) levels were associated with a higher degree of stenosis. The association between Lp(a) concentration and these vulnerable plaque characteristics supports the hypothesis that Lp(a) has a role in the process of atherosclerosis ( 56 ).…”
Section: Discussionsupporting
confidence: 73%
“…In women, elevated plasma Lp(a) levels were associated with higher prevalence of IPH and in men, elevated Lp(a) levels were associated with a higher degree of stenosis. The association between Lp(a) concentration and these vulnerable plaque characteristics supports the hypothesis that Lp(a) has a role in the process of atherosclerosis ( 56 ).…”
Section: Discussionsupporting
confidence: 73%
“…Lp(a) has shown to be proinflammatory, proatherogenic, prothrombotic, and antifibrinolytic potential, and promote atherosclerosis 6. Recent studies demonstrated that elevated (Lp(a)) concentrations was correlated to greater degree of carotid artery stenosis and plaque progression 12 13. Our study further demonstrated that elevated Lp(a) was associated with high odds of presence and burden of intracranial atherosclerosis.…”
Section: Discussionsupporting
confidence: 72%
“…Lp(a) was shown to be proatherogenic and may promote atherosclerotic cardiovascular diseases 7–11. Previous studies also have demonstrated that high Lp(a) level was related to carotid atherosclerosis,12 13 atherothrombotic stroke14 and ischaemic stroke 7 8 15 16. In contrast, few study investigated the association of Lp(a) level with cerebral small vessel diseases (cSVD).…”
Section: Introductionmentioning
confidence: 99%
“…Our systematic review indicated that compared with placebo or no treatment, MHT could significantly decrease the concentrations of TC, LDL-C, and Lp (a). Lp(a) is an independent risk factor for CVD and recurrent ischemic stroke ( Nordestgaard et al, 2010 ), the previous study showed the similar result of MHT on Lp(a) with us ( van Dam-Nolen et al, 2021 ). As for the TG concentration, previous study had showed that MHT could significantly increase it ( Stevenson et al, 2015 ).…”
Section: Discussionmentioning
confidence: 57%